2010
DOI: 10.1245/s10434-009-0906-6
|View full text |Cite
|
Sign up to set email alerts
|

Occult Contralateral Carcinoma in Patients with Unilateral Papillary Thyroid Microcarcinoma

Abstract: Based on our findings, total thyroidectomy, including the contralateral lobe, should be considered for the treatment of unilateral PTMC if it presents as a multifocal tumor in the unilateral lobe and/or if nodules are found in the contralateral lobe during preoperative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
53
3
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 17 publications
19
53
3
6
Order By: Relevance
“…Some previous studies reported similar findings to our study that ipsilateral multifocal disease was the predictive factor for contralateral cancer in PTMC [16]. But the relation between multifocality and LN metastasis or recurrence is controversial.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some previous studies reported similar findings to our study that ipsilateral multifocal disease was the predictive factor for contralateral cancer in PTMC [16]. But the relation between multifocality and LN metastasis or recurrence is controversial.…”
Section: Discussionsupporting
confidence: 90%
“…For PTMC, up to 40% of patients have been reported to have contralateral carcinoma at the time of histological review, but these incidence show a considerable difference according to study population [14,15]. In our results, 19.6% of PTMC had contralateral carcinoma and this incidence is consistent with previous study restricted to those with preoperatively unilateral confined PTMC [16].…”
Section: Discussionsupporting
confidence: 90%
“…Neck metastases were found in 51/101 (50.5%) participants, in 19 (37.3%) ofwhom the lateral compartment was also affected, agreeing with other authors' reports. No participant exhibited metastases contralateral to the primary tumor, which is also asomewhat rare finding in other studies (9.8-18.9%) [8][9][10]. The patients with neck metastasis had more dissected lymph nodes than theones without metastasis (p = 0.01), but the lymph node size did not differ betweengroups (p = 0.34).…”
Section: Discussionsupporting
confidence: 69%
“…In the absence of a clear consensus, the decision on the extent of thyroidectomy and the role of RAI is always one that should be made between the patient, surgeon, and endocrinologist, as reflected in the present results. About 30% of patients with low-risk WDTC harbor contralateral cancers (12,13). While the clinical relevance of these cancers is still unclear, these tumors may represent multicentricity or intrathyroidal spread (14,15).…”
Section: Figmentioning
confidence: 99%